Descriptive representation and attitudes about local government: An experimental test using real-world stimuli - David Doherty; Madeline Schade; Dana Garbarski (Research & Politics)
Does descriptive representation lead people to evaluate elected officials and their institutions more favorably? Does it improve political efficacy and engagement? We report findings from a survey experiment that uses treatments drawn from respondents’ real political context—elected officials who make policy in respondents’ county of residence. Specifically, we present a sample of Cook County residents with a member of the Cook County Board of Commissioners—who may or may not “match” the respondents gender or ethnoracial identity—to assess whether signaling that the respondent is “descriptively represented” on the Board affects their assessments of the Board and other attitudinal outcomes. Our pre-registered design positions us to identify effects of roughly one-eighth of a standard deviation in our full sample, but the estimated effects of signals of ethnoracial- and gender-based descriptive representation are null across the five outcomes we consider. In pre-registered exploratory analysis re-estimating effects by subgroup, we find evidence that suggests that descriptive representation affects some attitudes among women and Black respondents. This said, the effects we find in these groups are modest in magnitude, scattered, and, in most cases, statistically indistinguishable from those that emerge in other groups.